2014
DOI: 10.1016/j.visres.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative geometric mechanics lens model: Insights into the mechanisms of accommodation and presbyopia

Abstract: This study expands on a geometric model of ocular accommodation (Reilly and Ravi, Vision Res. 50:330-336; 2010) by relaxing assumptions regarding lens symmetry about the equator. A method for predicting stretching force was derived. Two models were then developed: Model 1 held the equatorial geometry constant at all stages of accommodation, while Model 2 allowed localized deformation at the equator. Both models were compared to recent data for axial thickness, anterior and posterior radii of curvature, surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 67 publications
3
12
0
1
Order By: Relevance
“…Gross lens shape change caused by strain results microstructural level changes in all the regions of the lens that we examined. This provides critical information that will be useful in expanding current biomechanical models of lens shape changes (Reilly and Ravi, 2010;Reilly, 2014;Wang et al, 2017). Furthermore, the identification of a relationship between microstructure and tissue biomechanics supports the idea that age-dependent microstructural alterations, such as an increase in stiffness of cells or matrix (Starodubtseva, 2011;Lacolley et al, 2017), could have biomechanical consequences at the tissue level.…”
Section: Discussionsupporting
confidence: 53%
“…Gross lens shape change caused by strain results microstructural level changes in all the regions of the lens that we examined. This provides critical information that will be useful in expanding current biomechanical models of lens shape changes (Reilly and Ravi, 2010;Reilly, 2014;Wang et al, 2017). Furthermore, the identification of a relationship between microstructure and tissue biomechanics supports the idea that age-dependent microstructural alterations, such as an increase in stiffness of cells or matrix (Starodubtseva, 2011;Lacolley et al, 2017), could have biomechanical consequences at the tissue level.…”
Section: Discussionsupporting
confidence: 53%
“…4 The age-related changes in lens size and shape contribute to presbyopia and cataracts. [5][6][7][8] The driving force(s) for this continuous growth remain unknown, at least in part due to technical challenges with reproducing the lens' complex in vivo environment which includes biochemical and biomechanical influences. Flat-mount lens explants are frequently used to probe specific aspects of LEC behavior, but may not be appropriate for examining mechanobiological behavior due to altered cell morphology 9 and mechanical environment.…”
mentioning
confidence: 99%
“…Tscherning [19] suggested that the zonule fibres compressed the lens rather than relaxing it, and Schachar [20] has proposed that outward tension from the zonule fibres around the lens equator could flatten the outer zones of the lens, causing the centre to bulge, in the manner of a squeezed balloon. However, mechanical modelling, based on the most recent curvature data [21], has come down firmly in favour of the Helmholtz model, in which the curvature changes in the lens are the result of relaxation of the zonule.…”
Section: Helmholtz and Accommodationmentioning
confidence: 99%